IS SUBCLINICAL HYPOTHYROIDISM IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME ASSOCIATED WITH BMI? - Yasar, H.Y. (Acta Endocrinol (Buchar), 2016)
OBJECTIVE: To investigate the impact of body weight on the subclinical hypothyroidism observed in patients with PCOS. METHODS: The study included 95 normal weight (Group-1) and 122 overweight or obese women (Group-2) with PCOS. The control group consisted of age and BMI matched healthy individuals and grouped as normal weight (n: 66, Group-3) and overweight or obese (n: 65, Group-4. Women with chronic disease such as overt thyroid dysfunction, late-onset adrenal hyperplasia, and diabetes were excluded from the study. Plasma glucose and lipid profile, thyroid hormones, insulin, FSH, LH, total testosterone, estradiol, progesterone and DHEA-S were measured. RESULTS: While fasting glucose was similar, insulin and HOMA-IR were higher in Group-2 and Group-4 (p: 0.001). The groups were similar with respect to FSH, Estradiol, prolactine, DHEAS. While total testosterone and LH levels were higher (ptestosterone: 0,009), progesterone was lower in both PCOS groups (pprogesterone: 0.041). Free T3, free T4, thyroid antibodies were similar between the groups, but the prevalence of subclinical hypothyroidism was greater in Group-2 and -4 than in Group-1 and -3 (p: 0.044). TSH was only correlated with BMI (r: 0.122, p: 0.02). CONCLUSION: The increased prevalence of subclinical hypothyroidism in women with PCOS might be the result of increased BMI.